2020
DOI: 10.1016/j.ijcha.2019.100437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxidative posttranslational modifications of SERCA2 on heart failure exacerbation in young patients with non-ischemic cardiomyopathy: A pilot study

Abstract: BackgroundOxidative posttranslational modifications (OPTM) impair the function of Sarcoplasmic/endoplasmic reticulum (SR) calcium (Ca2+) ATPase (SERCA) 2 and trigger cytosolic Ca2+ dysregulation. We investigated the extent of OPTM of SERCA2 in patients with non-ischemic cardiomyopathy (NICM).Methods and resultsEndomyocardial biopsy (EMB) was obtained in 40 consecutive patients with NICM. Total expression and OPTM of SERCA2, including sulfonylation at cysteine-674 (S-SERCA2) and nitration at tyrosine-294/295 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…SERCA2 is the only known molecular pump mediating calcium reuptake and is thus critically responsible for buffering intracellular calcium transients 51 . Oxidation of SERCA2 promotes its inactivation, a phenomenon that contributes to cardiomyocyte stiffness during heart failure 24 , 25 . Western blotting (Figure 4 F-H) showed that H/R promoted SERCA2 oxidation at Cys-674, an effect that was accompanied with a drop in SERCA activity (Figure 4 I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SERCA2 is the only known molecular pump mediating calcium reuptake and is thus critically responsible for buffering intracellular calcium transients 51 . Oxidation of SERCA2 promotes its inactivation, a phenomenon that contributes to cardiomyocyte stiffness during heart failure 24 , 25 . Western blotting (Figure 4 F-H) showed that H/R promoted SERCA2 oxidation at Cys-674, an effect that was accompanied with a drop in SERCA activity (Figure 4 I).…”
Section: Resultsmentioning
confidence: 99%
“…Sarco(endo)plasmic reticulum Ca 2+ -ATPase-2 (SERCA2) is the primary mechanism for Ca 2+ uptake into the SR/ER 20 , 21 . SERCA2 oxidation at Cys-674 promotes SERCA2 degradation and thus increases baseline intracellular calcium levels 22 , 23 , a pivotal phenomenon in myocardial dysfunction during heart failure 24 , 25 . Moreover, decreased SERCA2 expression has been found to contribute to IRI-related microvascular damage 14 , 26 - 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The functional abnormalities in ventricular CM that we observed can relate to T1Dinduced oxidative stress and glycosylation, which can directly affect CM contractility by modifying sarcomeric proteins [59] or impact Ca 2+ -handling proteins [60].…”
Section: Interventricular Alterations Promoted By Type 1 Diabetesmentioning
confidence: 86%
“…Modified natural LDL components such as apoβ, a surface protein of LDL, improve the ability of LDL to attach to its receptor [24]. In contractile failure, the contractility is altered by the oxidation of Sarco and endoplasmic Ca+2-ATPase as well as contractile proteins, including tropomyosin and actin [25,26]. The impact of ROS on endothelium underpinning molecules that can induce death, inflammation, and therefore clotting plaque formation in atherosclerosis makes oxidative stress a critical characteristic of CVD, which is also characterized as an initial causal component [27,28].…”
Section: Cvd Concerning Oxidative Stressmentioning
confidence: 99%